2008
DOI: 10.1097/mpg.0b013e31815604cd
|View full text |Cite
|
Sign up to set email alerts
|

12‐Month Follow‐up After Successful Infliximab Therapy in Pediatric Crohn Disease

Abstract: These data indicate that IFX is efficacious in controlling severe pediatric CD; however, to induce and maintain clinical remission, repeated IFX infusions are required, with a need for dose adjustment in a substantial number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 27 publications
4
41
0
1
Order By: Relevance
“…With the exception of the study by Sorrentino et al, 35 in which endoscopic remission was reported (100% remission at 80 weeks), most studies only provided rates of clinical remission/ response after re-treatment; in many cases, the information was restricted to the response rates, with no further details. 42,43,50,51,54,58,59,62 The studies by Molnar et al 43 and Monterubbianesi et al 51 reported the lowest response rates (54.7% and 63.3%, respectively) and the highest infusion reaction rates (6% and 10%, respectively). Excluding these studies, remission was safely achieved in a high proportion of patients in all other studies (ranging from 78.3% to 100%).…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of the study by Sorrentino et al, 35 in which endoscopic remission was reported (100% remission at 80 weeks), most studies only provided rates of clinical remission/ response after re-treatment; in many cases, the information was restricted to the response rates, with no further details. 42,43,50,51,54,58,59,62 The studies by Molnar et al 43 and Monterubbianesi et al 51 reported the lowest response rates (54.7% and 63.3%, respectively) and the highest infusion reaction rates (6% and 10%, respectively). Excluding these studies, remission was safely achieved in a high proportion of patients in all other studies (ranging from 78.3% to 100%).…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%
“…A study in a pediatric population found high relapse rates of 75% and 73% in the induction and maintenance groups, respectively, after 1 year. 42 The other 2 studies 40,41 reported relapse rates of 22% to 29% (induction group) and 31% to 44% (maintenance group) after 1 year; the difference between the groups was not statistically significant. Molnar et al found a similar relapse rate of 45% in a study of withdrawal after 3 induction doses of infliximab.…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not know if it was the effect of individual metabolism of the drug or if it was conditioned by other factors. Another problem occurring in the process of biological therapy is the fact that frequently it is necessary to intensify and prolong the treatment [18,21]. This concerns about 50% of patients, typically after 12 months of therapy, but it can happen earlier.…”
Section: Gojenie śLuzówkowe Po 9 Dawkach Ifx (3 Dawki Indukującementioning
confidence: 99%
“…Even more promising results of applying the therapy in children have been published in the last two years. In French studies Wynands et al [18] observed clinical remission in the 3 rd month of therapy, after 3 IFX doses in 36 of 38 treated children (95%). Ruemmele et al [9] described such clinical effect as a result of induction therapy in 85% of patients.…”
Section: Gojenie śLuzówkowe Po 9 Dawkach Ifx (3 Dawki Indukującementioning
confidence: 99%